Patriotic lyrics in folk tradition implications of national history - Jose, Vivencio R. (2001)
Just as great historic events impel people to band together in movements to achieve certain objectives and act accordingly, so do they inspire artists to express their sentiments and ideals in songs. The songs thus produced were sung by participants and sympathizers during their historic activities. Some of these songs may continue being sung in certain areas where they take roots; after a time, through repetition, they become a tradition among sectors deeply affected by the events. Surviving participants not surprisingly remember these songs. But there are others who, though they were not involved, grew up in a cultural milieu suffused by such songs. They nurture the lyric traditions which they transfer to the next generation. For this reason, some of these are still alive today. Though the conditions that earlier inspired the creation of these songs had already disappeared in their appointed time and place, the songs, in a seemingly autonomous manner, endure in the folk's cultural environment. This paper will discuss the lyrics of these songs- let others work on their melodies- as these have necessary implications on historiography and the writing of national history.